Understanding and managing public organizations - Rainey, Hal G. (San Francisco Pfeiffer Imprints, 2014)
"This revised edition of the best-selling text in the field includes a guiding framework of organizational analysis emphasizing the integration and coordination of the domains of the organization with the motivations, work attitudes, and behaviors of the people who lead them. Includes new research and practice from the US and internationally in collaboration and networks, innovation, process improvement through IT, open government and citizen participation, customer service, and a provides a greater emphasis on management practice through illustrative examples of those who are leading successful change efforts"
Includes bibliographical references and index.
Keywords: Public administration